Influence of Product Quality and Brand Image on Purchasing Decisions at My Bakery in Semarang City - Annisa Budi Utami; Mellasanti - Ayuwardani (Politeknik Negeri Semarang, 2023)
The easier the culinary business is, the more competition it has to face, including the bakery culinary business. The tight competition between these business actors continues to try hard to retain consumers and get new consumers to buy their products. Along with the increasingly intense competition, it has led to purchasing decision behavior made by consumers. The purpose of this study was to analyze the effect of product quality and brand image on purchasing decisions, both simultaneously and partially. The research sample was 78 respondents selected using purposive sampling technique. This study uses the Purposive Sampling method with 78 respondents as the sample. The data collection methods used are interviews, questionnaires and literature studies. The results showed that partially the product quality variable had a significant effect on purchasing decisions and brand image had a significant effect on purchasing decisions. The result of the calculation of the coefficient of determination between the variables of product quality and brand image on purchasing decisions is 0.645, this means that product quality and brand image have an influence of 64.5% on purchasing decisions, the remaining 35.5% is determined by other variables not examined